A escrita feminina na lírica de Maria Teresa Horta - Souza, Natália Salomé de (2015)
In the search for writings by women that talked about the female body I found Maria Teresa Horta’s lyric. In her poems, the eu-lírica gives voice to a body as a way to untie it from the patriarchal domain. Thus, there is a woman’s voice and a woman’s writing that derive from an immanence. They are analyzed, at first, from an internal movement that will answer some essential questions, such as: what makes this writing truly feminine? In what aspects is it different from a masculine one? Is it a biological manifestation or is this concept not founded in such perspective? According to the ideas of Hélène Cixous and Luce Irigaray, theoreticians of the difference feminism, there is a ‘woman being’ that has constantly been erased by the “father”’s and the logos’s laws, therefore women’s writing and speech need to subvert phallogocentrism and let themselves flow through female body. It would be the return of the semiotic language of Kristeva, essentially feminine and circular, which is not tied to the denomination and immobility of the name. In a poetic and erotic language, we find this speech of the body that surpasses an imposed social order, thus leading us to a second movement – an external one. The implications of a recovery of the female body by women outside the patriarchal sovereign would lead to a complete change in society, in which men and women would not occupy vertical spaces; on the contrary, their social positions would be established in a horizontal axis with no hierarchy, so women would not be subordinated to men and vice-versa. There would be mutual respect inside the difference. Politically, gender difference would not be a reason for discrimination and subordination. Hence, poetry represents the possibility of subversion of the patriarchal order from the phallus, as long as, when produced by women, it is the writing of a female body, a woman’s writing that voices the eu-lírica. From the becoming of a woman, women’s lyrics is born. Similarly, there comes gynocritics– a literary theory that marks a women’s tradition in the literary studies that rejects traditional criticism.